Revivalisme Kekuatan Familisme dalam Demokrasi: Dinasti Politik di Aras Lokal - Djati, Wasisto Rahajo (UI Scholars Hub, 2013)
The article aims to elaborate political dynasty that developed in local politics arena. The emergence of political dynasty is indicated by several points. First of all, the failure of function from local political party to conducts political regeneration. Secondly, high cost democracy which impeding public to participate in public office succession. Third, political power from local elite was uneven, thus resulting power centralization in few strong local elite that transforming dynasty. Patrimonialism is not always becoming main perspective to analyzing political dynasty. There are many alternative political perspectives to analyze this case. This paper used familism political culture to elaborate political dynasty in local politics arena. The result of this research shows political preference from the local leader is considered to choose his family member in governmental succession to cover up his political sins. Familism also influenced from political source such as tribalism, populism, and feudalism that distinguishing local political dynasty in Indonesia.